ECONOMIC RETURN, YIELD AND HARVEST INDEX OF INTEGRATED NITROGEN IN 85,000 PLANTS Ha-1 ON Zea mays AGRIBUSINESS IN PESAWAR, PAKISTAN - Farhan Ahmad; Ristina Siti Sundari; Junaid Ahmad; Muhammad Shafi (Hexagro Journal, 2021)
Zea mays is one of staple food for population in the world. The research aimed to determine economic return of integrated nitrogen and plant density. The research was conducted in RCB design having split plot arrangement comprising four replications. Plant density of Azam variety Maize were alloted to main plots (65000, 75000 and 85000 ha-1). Integrated nitrogen were assigned to sub-plots (control, 0% FYM + 100 % Urea, 100 % FYM + 0 % Urea, 50 % FYM + 50 % Urea, 75 % FYM + 25 % Urea and 25 % FYM + 75 % Urea). Data were recorded on plants harvest, harvest index, and benefit-cost ratio. The result showed plant density of 85.000 ha-1 among integrated nitrogen application of 50 % FYM along with 50% urea produced the highest B/C ratio (6.2). It is concluded that 50% FYM + 50% Urea along with plant population of 85000 plants ha-1 enhanced yield. Harvest index 33,4%, yield 4219.44 kgha-1. Total cost 36.961PKR, total income 227.941PKR economic net return 190.980PKR.